Ida'at hawla turath al-gharb al-Islami wa tarikhihi al-iqtisadi wa al-ijtima'i - Butshish, Ibrahim al-Qadiri (Beirut : Dar al-Tali'ah, 2002)
Africa, North; Andalusia (Spain); social life; economic conditions; civilization; history; 647-1517
Keywords: Africa, North -- Economic conditions; Africa, North -- Social conditions; Africa, North -- History -- 647-1517; Andalusia (Spain) -- Civilization